Severity of depressive but not anxiety symptoms impacts glucose metabolism among patients with type 2 diabetes in primary care - Hargittay, Csenge; Eöry, Ajándék; Márkus, Bernadett; Mohos, András; Ferenci, Tamás; Vörös, Krisztián; Rihmer, Zoltán; Gonda, Xenia; Torzsa, Péter (Frontiers in Medicine, 2022)
Background: Data from primary care regarding the prevalence of symptoms of depression and anxiety, and their effect on glycemic control among people with diabetes is lacking in Hungary. The recently introduced Patient Health Record (PHR) requires family doctors to screen for depressive symptoms. Objectives: We aimed to investigate the prevalence of depressive and anxiety symptoms among patients with type 2 diabetes in the general practice, and the relationship between these affective disorders and glycated hemoglobin (HbA1c) level. Methods: We included 338 consecutive patients with type 2 diabetes from six primary care practices in this cross-sectional study. A self-administered questionnaire (patient history, anthropometric, socioeconomic, laboratory parameters), the Beck Depression Inventory (BDI) and the Hamilton Anxiety Scale (HAM-A) were used. Results: The mean age of the sample was 64.0 ± 11.5 (years ± SD), 61% of participants were female. The prevalence of depressive symptoms was 21%, mainly moderate/severe symptoms (13%). Anxiety symptoms were more common (35%). We found significant univariate association between the depressive symptoms and HbA1c (p=0.001), suicide attempt (p<0.001), anxiety (p<0.001), micro- and macrovascular complication (p=0.028 and p<0.001), education (p=0.001) and place of residence (p=0.002). In multivariate analysis, however, only BDI score had significant (p=0.03191) association with glycemic control. Conclusions: Among primary care patients with type 2 diabetes, the prevalence of depressive symptoms was less frequent than anxiety symptoms. More severe depressive symptoms were associated with worse glycemic control.